U.S. border enforcement and the net flow of Mexican illegal migration - Manuela Angelucci (Institute for the Study of Labor (IZA), 2005)
This paper investigates the effect of U.S. border enforcement on the net flow of Mexican undocumented migration. It shows how this effect is theoretically ambiguous, given that increases in border controls deter prospective migrants from crossing the border illegally, but lengthen the duration of current illegal migrations. It then estimates the impact of enforcement on 1972-1993 migration net flows by merging aggregate enforcement data with micro data on potential and current illegal Mexican migrants. The econometric model accounts for the endogeneity of border controls using the Drug Enforcement Administration budget as an instrumental variable. Both the inflow and outflow of illegal Mexican migration are highly sensitive to changes in border enforcement. The estimates of the enforcement overall effect on illegal migration's net flow range across different specifications, from a decline - about 35% of the size of the effect on the inflow - to an increase. Thus, they suggest that border enforcement may not be an effective means to reduce the level of the illegal alien population in the United States.
Keywords: F22; J61; K42; O15; 330; illegal migration; border enforcement; Mexico